EFEKTIVITAS PEMANFAATAN EDMODO DALAM PEMBELAJARAN GEOGRAFI PADA MATERI PENGETAHUAN DASAR PEMETAAN KELAS X IPS SMAN 7 PADANG - maya kumala sari; Nofrion Nofrion (JURNAL BUANA, 2020)
This research is purpose to knowing the effectiveness of ultilization Edmodo in Geography learning to basic knowledge material mapping of class X IPS SMAN 7 Padang that was reviewed from the interest student of learning process, the involvement student of learning process and the result of learning process.The kind of this research was used the quasi experimental design. The technic of data analysis 1) The descriptive analysis percentages was used to analyzed the interest and involvement of learning student, 2) The inferential statistical analysis was used to analyzed the result of learning student. The result of this reseach was indicate that : 1) The interest of student class X IPS SMA Negeri 7 Padang in learning geography in used Edmodo media reside in the high category with a percentage of 78%. 2) The involvement of student in geography learning in used Edmodo reside in the high category with a percentage 70,80%, whereas the involment of student in geography learning that use the conventional media reside in the low cegory with a percentage 62,28%. There are differences result in learning process of the student with the experimental class outcomes of the experimental class with the control class with the average acquisition of experimental class learning outcomes of 81.78 while the control class of 72.11. This is supported by testing the hypothesis by acquisition thitung> ttabel yaitu 4,789 > 2,000 dan Sig. < Sig.α (0,000 < 0,05), then Ho was rejected and Ha was received. 4) The ultilization of Edmodo was enough effective to increas the result of student learning in basic knowledge material mapping class X IPS at SMA 7 Padang with the result of N-Gain as big as 58,84%.